THE EFFECT OF PENTAGON'S FRAUD ON PROFIT MANAGEMENT - Ana Mardiana; Paulus Tangke; Lukman Lukman (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – The purpose of this study was to analyze the effect of pentagon fraud towards earnings management. The fraud pentagon consists of 5 factors that influence the occurrence of fraud, namely: pressure, opportunity, rationalization, capability, and arrogance. Design/methodology/approach – Multiple regression analysis was used to analyze the data and hypothesis testing was performed using a partial test (t test). Findings – The results of this study indicate that the five fraud pentagon factors, namely: pressure, opportunity, rationalization, capability, and arrogance have a positive and significant effect on earnings management. The results show that an increase in each factor will significantly improve earnings management in manufacturing companies in Indonesia in the 2018-2020 period. Originality – The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. Keywords: Arrogance, Capability, Earnings Management, Pentagon Fraud, Pressure, Opportunity, Rationalization Paper Type Research Result